The impact of electronic interactive teaching materials (EITMs) in e-learning on junior high school students' critical thinking skills. (December 2022) - Sinaga, Parlindungan; Setiawan, Wawan; liana, Mey
Abstract: This study aimed to examine the impact of electronic interactive teaching materials (EITMs) distributed and operated on students' mobile phones. In improving their critical thinking skills, compared to electronic textbooks using the theme of food and health. To this end, a quantitative research method with a quasi-experimental design was chosen. The sample was determined with the purposive sampling technique and consisted of junior high school students who are divided into the experimental class and control class, of 23 students each. The instruments used included a critical thinking ability test and a four-rating scale questionnaire. The data were analysed by determining the average normalized gain, t -test means, and effect size, and descriptively analysing the questionnaire. The results of data analysis show that (1) The critical thinking skills of the experimental group increased with high criteria, and the control group increased with medium criteria. (2) The increase in the critical thinking skills of students who used the EITMs, both in the overall and per-item mean scores, was higher than that of students who used electronic textbooks; (3) There was a significant difference in the increased critical thinking skills between the experimental class and control class, and (4) Students responded positively to the EITMs stored and operated on their individual mobile phones.